INTEGRATED STRATIGRAPHY OF MIDDLE-LATE MIOCENE SYNOROGENIC DEPOSITS OF THE EASTERN SOUTHERN APENNINE CHAIN: THE SAN BARTOLOMEO FLYSCH (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The present paper deals with the stratigraphic and biostratigraphic study of the middle-late Miocene thrust-top basin deposits of the San Bartolomeo Flysch, exposed north of Matese mountains and analysed during the geological survey of the sheet N° 405 Campobasso of the new Geological Map of Italy, 1:50.000 scale. The integrated study of calcareous nannofossils and planktonic foraminifera, based on the semi-quantitative distribution range of index species, revealed the presence of age-diagnostic assemblages which are comparable with those of different middle-late Miocene deep-marine sedimentary settings of the Mediterranean Basin. The biostratigraphic dataset suggests an early Serravallian – early middle Tortonian age. In terms of calcareous nannofossil biostratigraphy, the studied succession falls between the Last Occurrences of Sphenolithus heteromorphus and the First Occurrence of Discoaster bellus gr., corresponding to the MNN6 – MNN8 zone interval. In terms of planktonic foraminiferal biostratigraphy the studied sediments fall between the Last Occurrence of Globorotalia peripheroronda and the First Regular Occurrence of Neogloboquadrina acostaensis, corresponding to the MM6 p.p. - MMi10 p.p. zone interval. This study documents the applicability of the recent Mediterranean middle –late Miocene biozonations for the biostratigraphic study of siliciclastic synorogenic sediments, and challenges the most recent studies that dated the San Bartolomeo Flysch to the late Tortonian- early Messinian.
Keywords: Calcareous plankton biostratigraphy; Middle and Late Miocene; Mediterranean; San Bartolomeo Flysch; Southern Apennines